Analysis of the Level of Competitiveness of Indonesian Mangosteen, Mango, and Guava Exports in the International Market - Yustina Medy Rosila Christy; Ni Ketut Budiningsih (Asosiasi Riset Ekonomi dan Akuntansi Indonesia, 2025)
Non-oil and gas exports play a crucial role in Indonesia's economy, particularly due to their more stable and increasing contributions compared to oil and gas exports, which are vulnerable to fluctuations in global oil prices. This research aims to: 1) determine the comparative advantage of Indonesia's mangosteen, mango, and guava exports in the international market; 2) assess the competitive advantage of these exports; and 3) evaluate the level of trade specialization in Indonesia's mangosteen, mango, and guava exports in the international market. The data used in this study is secondary data related to the exports of mangosteen, mango, and guava from Indonesia during the period of 2013-2023. The data analysis techniques employed include descriptive analysis and quantitative analysis using the Revealed Comparative Advantage (RCA) approach, Export Competitiveness Index (ECI), and Specialization Index (ISP). The results indicate that Indonesia has a strong comparative advantage in the international market, a strong competitive advantage, and is positioned as a leading exporter of mangosteen, mango, and guava.